Design and development of a 200 W converter for phosphoric acid fuel cells - Kuyula, Christian Kinsala (My University, 2013)
“If we think oil is a problem now, just wait 20 years. It’ll be a nightmare.” — Jeremy Rifkin, Foundation of Economic Trends, Washington, D.C., August 2003. This statement harmonises with the reality that human civilisation faces today. As a result, humankind has been forced to look for alternatives to fossil fuels. Among possible solutions, fuel cell (FC) technology has received a lot of attention because of its potential to generate clean energy. Fuel cells have the advantage that they can be used in remote telecommunication sites with no grid connectivity as the majority of telecommunication equipment operates from a DC voltage supply. Power plants based on phosphoric acid fuel cell (PAFC) have been installed worldwide supplying urban areas, shopping centres and medical facilities with electricity, heat and hot water. Although these are facts regarding large scale power plants for on-site use, portable units have been explored as well. Like any other fuel cell, the PAFC output power is highly unregulated leading to a drastic drop in the output voltage with changing load value. Therefore, various DC–DC converter topologies with a wide range of input voltages can be used to regulate the fuel cell voltage to a required DC load. An interleaved synchronous buck converter intended for efficiently stepping down the energy generated by a PAFC was designed and developed. The design is based on the National Semiconductor LM5119 IC. A LM5119 evaluation board was redesigned to meet the requirements for the application. The measurements were performed and it was found that the converter achieved the expectations. The results showed that the converter efficiently stepped down a wide range of input voltages (22 to 46 V) to a regulated 13.8 V while achieving a 93 percent efficiency. The conclusions reached and recommendations for future research are presented.
M. Tech. (Engineering: Electrical, Department Electronic Engineering, Faculty of Engineering and Technology), Vaal University of Technology,
Keywords: Fuel cells; Telecommunication equipment; Clean energy; Interleaved synchronous buck converter; 621.312429; Fuel cells; Renewable energy resources